1999
DOI: 10.1243/0954407991527161
|View full text |Cite
|
Sign up to set email alerts
|

Study of combustion characteristics of a compression ignition engine fuelled with dimethyl ether

Abstract: This paper presents the combustion characteristics of a light-duty direct-injection diesel engine operating on dimethyl ether (DME). The indicated pressure diagrams and injector needle lifts are recorded and the combustion characteristics are demonstrated and compared with those of an engine operated on diesel fuel. The experimental and calculated results show that the DME engine has a longer delay of injection and duration of injection, a lower maximum cylinder pressure and rate of pressure rise, as well as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(34 citation statements)
references
References 4 publications
2
32
0
Order By: Relevance
“…The equivalence ratio of the conventional diesel u-T map for soot emission to appear is 2, but the equivalence ratio of the DME u-T map for soot emission to appear is 3. Therefore the experiments on engines fuelled with DME result in soot-free combustion [6,27,28]. This is because of the high oxygen content in DME fuel, which agrees well with experimental findings that the formation of soot precursors in combustion decreases with increase in the oxygen content in the fuel [29][30][31].…”
Section: Homogeneous Reactor Modelling Resultssupporting
confidence: 86%
“…The equivalence ratio of the conventional diesel u-T map for soot emission to appear is 2, but the equivalence ratio of the DME u-T map for soot emission to appear is 3. Therefore the experiments on engines fuelled with DME result in soot-free combustion [6,27,28]. This is because of the high oxygen content in DME fuel, which agrees well with experimental findings that the formation of soot precursors in combustion decreases with increase in the oxygen content in the fuel [29][30][31].…”
Section: Homogeneous Reactor Modelling Resultssupporting
confidence: 86%
“…When the speed is 1 400 r/min, both the maximum pressure of the DME The ignition delay of DME is shorter than that of diesel, which results in the lower cylinder pressure of DME. A previous study revealed that the velocity of sound in DME fuel is 980 m/s, which is lower than that in diesel fuel (1 330 m/s), which means that the pressure wave propagation will be longer in the DME engine than that in the diesel engine, and consequently the DME engine will have a longer fuel injection delay than the diesel engine [7]. The longer injection delay of DME results in the lagged maximum pressure.…”
Section: Comparison Of Brake Specific Fuel Consumptionmentioning
confidence: 95%
“…Therefore, DME is sufficiently suitable as a substitute of diesel. Due to these characteristics of DME, the spray, atomization, combustion and exhaust emissions of the DME fueled diesel engine system, as well as the applicability and properties of DME, have been investigated by many researchers [7][8][9].…”
Section: Introductionmentioning
confidence: 99%